Impact of Various Desiccants on Extending Groundnut Pod Storability - A USHA; R JERLIN; C TAMILARASAN (Seed Research, 2026)
Storability of seeds generally depend upon the moisture content, which need to be brought down even at high temperatures. During the storage of groundnut pods, for reduction of moisture content, use of suitable desiccants will be useful rather than going for the practice of pod drying methods, which will be useful for reduction as well as maintenance of low moisture content of pods for extending the storability. The study on the effect of storability of groundnut pods cv. VRI 8 with different desiccants viz., anhydrous calcium chloride (14 g kg-1), silica gel (8.5 g kg-1) and zeolite beads (300 g kg-1) in poly lined gunny bag under ambient condition were carried out in Department of Seed Science and Technology, TNAU, Coimbatore. The result revealed that the performance of stored seed was decreased with advancement in storage period. Among all the treatments, storage of pods with zeolite beads (300 g kg-1) was found to be supreme in maintaining low moisture content of 6.24% after six months of storage followed by silica gel (8.5 g kg-1) and anhydrous calcium chloride (14 g kg-1). The pods stored with zeolite beads (300 g kg-1) recorded higher germination per cent (78 per cent) and vigour index (2480), insect infestation (8 %) and pathogen infection (5 %). Hence, storage of groundnut pods with zeolite beads (300 g kg-1) can be practiced to extend the storability with minimum deterioration.